2021
DOI: 10.1186/s42523-021-00093-5
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of frugo-folivorous sifakas across environments

Abstract: Background Captive animals, compared to their wild counterparts, generally harbor imbalanced gut microbiota owing, in part, to their altered diets. This imbalance is particularly striking for folivores that fundamentally rely on gut microbiota for digestion, yet rarely receive sufficient dietary fiber in captivity. We examine the critically endangered Coquerel’s sifaka (Propithecus coquereli), an anatomically specialized, rather than facultative, folivore that consumes a seasonal frugo-folivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Translocated hosts seem to importantly represent a dynamic transitional state between the relative extremes of wild and captive environments, which induce changes in host gut microbiome diversity. Overall, previous studies agree that dietary differences between host captive and wild environments are one of the main factors driving some of these gut microbiome changes 5 , 13 18 , 18 , 19 , 69 , 70 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Translocated hosts seem to importantly represent a dynamic transitional state between the relative extremes of wild and captive environments, which induce changes in host gut microbiome diversity. Overall, previous studies agree that dietary differences between host captive and wild environments are one of the main factors driving some of these gut microbiome changes 5 , 13 18 , 18 , 19 , 69 , 70 .…”
Section: Discussionsupporting
confidence: 60%
“…More closely related hosts seem to share more similar microbiome communities than more distantly related hosts (i.e., phylosymbiosis) 6 , 7 , and gut microbiome communities are usually enriched for bacteria associated with the main macronutrients of a host’s feeding strategy 8 12 . Yet, environmental factors significantly alter individual host microbiomes 10 , 12 , as evidenced by differences in microbiome composition between wild and captive conspecifics across a variety of animal taxa 13 19 . Gut microbiome studies of captive and wild mammals show that non-human primates (NHPs) experience relatively large losses of native gut microbiome diversity in captivity compared to the wild 5 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…More closely related hosts seem to share more similar microbiome communities than more distantly related hosts (i.e., phylosymbiosis) 6,7 , and gut microbiome communities are usually enriched for bacteria associated with the main macronutrients of a host's feeding strategy [8][9][10][11][12] . Yet, environmental factors significantly alter individual host microbiomes 10,12 , as evidenced by differences in microbiome composition between wild and captive conspecifics across a variety of animal taxa [13][14][15][16][17][18][19] . Gut microbiome studies of captive and wild mammals show that non-human primates (NHPs) experience relatively large losses of native gut microbiome diversity in captivity compared to the wild 5,13 .…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing technology has made it possible to gain insight into the gut microbiota of a diverse range of animal species, including primates (Amato et al, 2013 ; Clayton et al, 2016 ; Greene et al, 2021 ), carnivores (An et al, 2017 ), reptiles (Tang et al, 2020 ), and birds (Roggenbuck et al, 2014 ; García-Amado et al, 2018 ), among others. The majority of all microbiome studies have been conducted on single species, which provide excellent conditions for investigating short-term exposure effects such as diet changes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have compared the microbiota of wild and captive animals. Studies in diverse animal species, including Antarctic seals (Nelson et al, 2013 ), various primates (Amato et al, 2013 ; Hale et al, 2019 ; Greene et al, 2021 ), and horses ( Equus ferus caballus ) (Metcalf et al, 2017 ) showed significant differences in the composition of the gut microbiota in wild individuals compared to captive relatives. Another study showed that primates living in captivity gain a more human-like microbiota composition over time (Clayton et al, 2016 ), and that this is reproducible between captive populations (Houtz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%